Correction: From linked open data to molecular interaction: studying selectivity trends for ligands of the human serotonin and dopamine transporter. Issue 7 (25th June 2019) - Zdrazil, Barbara; Hellsberg, Eva; Viereck, Michael; Ecker, Gerhard F.
Abstract : Correction for 'From linked open data to molecular interaction: studying selectivity trends for ligands of the human serotonin and dopamine transporter' by Barbara Zdrazil et al., Med. Chem. Commun., 2016, 7, 1819–1831.